Kikuchi–Fujimoto disease in an adolescent girl with discoid skin lesion and high serum ferritin - A rare case report from Odisha - Biswal, Sebaranjan; Dash, Arun Kumar; Kumar, Manoj; Mohakud, Nirmal Kumar (Indian Journal of Child Health, 2019)
Kikuchi–Fujimoto disease is a self-limiting disease which frequently appears with fever and lymphadenopathy, thus creating the need for differential diagnosis of persistent febrile lymphadenopathy. Although the cause of Kikuchi’s disease is unknown, some viral or bacterial infections or immunological conditions are attributed to it. It has occasionally been misdiagnosed as lymphoma or tubercular lymphadenitis; hence, clinicians should be made aware of this disease. We report a case of a 14-year-old female child who was presented with fever, rashes, multiple oral ulcers, and lymphadenopathy. The child was diagnosed as Kikuchi disease, on the basis of lymph node histopathology. There was a significant improvement of the clinical picture with oral prednisolone therapy for 2 weeks and tapering over the next 2 weeks.